In Vitro comparison in the antimicrobial effect between Ciprofloxacin and Neem leaf extract (Azadirachta indica) on Escherichia coli Growth (Bangladesh Journal of Medical Science, 2016)
Objective: Medicinal plants remain in vogue to treat some diseases in lower socio-economic communities, despite the availability of antimicrobials, often. Majority of rural Bangladeshi and tribal people being grossly illiterate and ignorant, use various herbs to treat a wide range of diseases. Of several medicinal-plants, neem is reported to have enormous impact in treating inflammation and infections. We, therefore, compared the antimicrobial effect of ethanolic neem leave extract (ENLE) on Escherichia coli (E. coli), with that of Ciprofloxacin. Materials & Methods: This experimental study compared the in vitro antimicrobial activity between ENLE and Ciprofloxacin on E. coli carried out in Department of Pharmacology and Therapeutics of SS-Medical College, Dhaka, Bangladesh. Antimicrobial efficacy of ENLE and ciprofloxacin (5µg; Oxoid, UK) was determined against E. coli following minimum inhibitory concentration. By filtration and evaporation of Neem leaves ENLE was prepared. Antibiotic Sensitivity Test was performed on Muller-Hinton agar using a twofold serial dilution. Results: ENLE showed an inhibitory effect on the growth of E. coli at the concentration of 3.125 mg/ml. Antibacterial susceptibility of E. coli was performed on MHA and diameters of zone of inhibition by both ENLE and Ciprofloxacin were measured after overnight aerobic incubation at 37°C. Diameter of zone of inhibition against E. coli was 28 ± 0.16 mm with ENLE, 36 ± 0.07 mm with Ciprofloxacin (5µg/disk) (p